Lipid peroxidation, antioxidant enzymes and pyruvate kinase activity in rats with carbon tetrachloride-induced cirrhosis - Yilmaz, S; Bahçeciogiu, IH (Tubitak Scientific & Technological Research Council Turkey, 2000)
Changes in the level of malondialdehyde (MDA, a degradative product of lipid peroxidation) and in the antioxidant defense system in rats with carbon tetrachloride-induced liver cirrhosis were studied, in order to determine whether there is any relation between these parameters and the disease. Liver cirrhosis was induced in Wistar-Albino rats by carbon tetrachloride (0.15 gr/100 gr body weight) which was injected subcutanously three times a week for six weeks. In the liver, the level of tissue malondialdehyde was analysed according to Yagi's method; and glutathione peroxidase, glucose-6-phosphate dehydrogenase, pyruvate kinase activities according to Beutler's method. The level of liver malondialdehyde in the group with cirrhosis was significantly higher than in the control group (p<0.05). Glutathione peroxidase and glucose-6-phosphate dehydrogenase activity was significantly lower in the group with cirrhosis than in the control group (p<0.05). The difference was not statistically significant for pyruvate kinase activity (p>0.05). Thus, we consider that cirrhosis causes changes in the antioxidant defense system and it can lead to oxidative stress and peroxidation.
Keywords: cirrhosis; lipid peroxidation; glutathione peroxidase; glucose-6-phosphate dehydrogenase; pyruvate kinase